ANÁLISIS FINANCIERO Y ESTUDIO DE CAPITAL DE TRABAJO DE LA LAVADORA, LUBRICADORA DE LA COOPERATIVA DE TRANSPORTES LOJA, DE LA CIUDAD DE LOJA, PERÍODOS 2015-2016 - Abad Camacho, Laura Elizabeth (2018)
The thesis entitled "FINANCIAL ANALYSIS AND STUDY OF THE WORKING CAPITAL OF THE WASHING MACHINE, LUBRICATOR OF THE LOJA TRANSPORTATION COOPERATIVE, OF THE CITY OF LOJA, PERIODS 2015-2016" aims to inform the partners of the lubricating machine about the situation economic-financial, through the application of Vertical and Horizontal Analysis, Financial Reasons, Study of Working Capital through the presentation of the respective financial reports that allow the correct and effective decision making. With the methodology used in the first objective, the financial structure was determined by identifying the economic situation and the variations presented by each one of the accounts that make up the statement of financial position and the income statement. For the development of the second objective, financial indicators were applied to determine the degree of liquidity, indebtedness and profitability, with the objective of knowing if the washing machine has financial solvency to cover its obligations and if the entity generates sufficient profitability. To comply with the third objective, a study of working capital was carried out by applying indicators that reflect the use of the operating resources of the lubricating machine. The fourth objective was the financial reports that detail, in summary form, the results obtained and the suggestions that are going to be taken into consideration by the partners of the washing machine. 5 Finally, it was concluded that in the analysis of the Lubricadora washing machine, in 2015 the final result shows a loss of $ - 645.73, while in 2016 a profit of $ 23,813 was generated, 46, that is to say, that in this year the annual income increased due to sales and the good administration applied in the entity. It is recommended that managers continue to increase sales through promotions, discounts, advertising, display of merchandise and improve sales prices to customers who buy cash and for large amounts, with the purpose that the final result allows reaching a level of utility that satisfies the objectives of the company, being necessary the continuous realization of the analysis and study of working capital. To evaluate the general management, the solvency, the rentability, the liquidity and its capacity to generate funds, allowing the opportune taking of decisions